Utilization of Digital Marketing in Maintain Brand Loyalty and Increasing Sales of Opak Oded - Anggini, Megah Dewi Anggini; Nurfonda, Alfi Novia (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
The focus of the research is on the use of digital marketing in maintaining brand loyalty and increasing sales opak oded. The aim of the research is to determine the use of digital marketing in maintaining brand loyalty and increasing Opak Oded sales, strategies for building consumer loyalty and the factors that hinder the use of digital marketing in maintaining brand loyalty and increasing Opak Oded sales. This research is motivated by the use of digital marketing which is an efficient way to promote and advertise products. Using data analysis carried out by Miles and Huberman (1984), namely data reduction, data presentation, and drawing conclusions. The results and discussion obtained by digital marketing are a form of activity to market or promote products using sophisticated technology, and in maintaining and maintaining brand loyalty for Opak Oded products, namely being able to create loyalty from consumers in terms of taste quality. This has continued for decades in sales of opaque oded products until now. Of course it will have a positive effect on increasing sales. Moreover, with good use of digital marketing, such as through advertising and successful endorsements, more profits can be obtained from increasing consumer demand.